Immunological and morphological analysis of heterotopic ossification differs to healthy controls - Trieb, Klemens (BMC Musculoskelet Disord, 2018)
BACKGROUND: Formation of lamellar bone in non-osseus tissue is a pathological process called heterotopic ossification. It is the aim of this study to analyse the morphology and immunological status of patients with heterotopic ossification compared to individual healthy persons. METHODS: Human bone marrow and blood samples were obtained from 6 systemically healthy individuals and 4 patients during resection of heterotopic ossification from bone at hip arthroplasty. Bone was fragmented and treated with purified collagenase. Immunofluorescence surface staining was performed and analyzed with flow cytometry. Microcomputed tomography scanning was done performed at a resolution of 11 and 35 μm isometric voxel size respectively using a two different cone beam X-computer tomography systems and a microfocus X-ray tube. Subsequently the volume data was morphometrically analysed. RESULTS: The monocytes, stem cells, stroma cells and granulocytes progenitor cells were strongly reduced in the heterotopic ossification patient. Additionally a significant reduction of stromal stem cells cells and CD34 positive stem cells was observed. The frequency of NK-cells, B cells and T cells were not altered in the patients with heterotopic ossification compared to a healthy person. Micromorphometric parameters showed a lower content of mineralized bone tissue compared to normal bone. Mean trabecular thickness showed a high standard deviation, indicating a high variation in trabecular thickness, anisotropy and reducing bone strength. CONCLUSIONS: This work shows altered immunological distribution that is accompanied by a low decrease in bone volume fraction and tissue mineral density in the heterotopic ossification sample compared to normal bone. Compared to healthy subjects, this might reflect an immunological participation in the development of this entity.